Comparison of Arabica Coffee Farming Income Between Partner Farmers of Koerintji Barokah Bersama Cooperative and Non-Partner Farmers in Gunung Tujuh District, Kerinci Regency - Febrilia, Kiki; Damayanti, Yusma; Effran, Endy (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to (1) Describe the Arabica coffee farming practices of partner and non-partner farmers of the Koerintji Barokah Bersama Cooperative in Gunung Tujuh District, Kerinci Regency (2) Analyze the income earned by Arabica coffee farmers who are partners and non-partners of the Koerintji Barokah Bersama Cooperative in Gunung Tujuh District, Kerinci Regency (3) Analyze the comparison of farm income between partner and non-partner Arabica coffee farmers of the Koerintji Barokah Bersama Cooperative in Gunung Tujuh District, Kerinci Regency. This research employed a quantitative approach using descriptive analysis and the independent samples t-test. Primary data were collected through a survey involving 94 respondents, consisting of 41 partner farmers and 53 non-partner farmers. The results of the study indicate that Arabica coffee farming in the study area is relatively good, despite differences in management aspects, particularly in the application of fertilizer and pesticide doses as recommended. The average farm income of partner farmers was Rp31,649,663 per hectare per year, while non-partner farmers earned Rp25,575,296 per hectare per year. The t-test results indicated a significant difference in income between the two groups (Sig. 0.018).